THE EFFECT OF KNOWLEDGE MANAGEMENT AND TRAINING PROGRAMS ON LECTURER INNOVATIVENESS AT VOCATIONAL PRIVATE UNIVERSITIES IN BOGOR - Taurusyanti, Dewi; Moeins, Anoesyirwan; Muharam, Hari (jfpublisher, 2023)
Lecturer innovativeness is one of the most important parts of educational innovation process, and assist the achievement of educational goals. Currently, lecturers' innovativeness needs to be improved, especially for vocational lecturers to initiate or improve a product, process, or service. The purpose of this research is to identify the effect of knowledge management and training programs on lecturers' innovativeness. This research was conducted lecturer of Vocational Universities in Bogor. The sample of this research was 100 lecturers from 6 Vocational Universities, and the sample determination used a proportional random sampling method to obtain representative data. This research uses SEM-Smart PLS data analysis techniques in quantitative research types. The results of this research found that knowledge management affects innovativeness with p-values of 0.000<0.05 and positive t-statistics values with tcount > ttable (7.013>1.96), and training programs affect innovativeness with p-values of 0.000 < 0.05 and positive t-statistics value with tcount > ttable (4.420>1.96). From the research result, it shows that knowledge management is directly predicted to increase innovativeness through application efforts and training programs is directly predicted to increase the innovativeness through the role of professional instructors.